2020
DOI: 10.1002/celc.202000120
|View full text |Cite
|
Sign up to set email alerts
|

Overpotential‐Dependent Volcano Plots to Assess Activity Trends in the Competing Chlorine and Oxygen Evolution Reactions

Abstract: The selectivity problem of the competing chlorine evolution (CER) and oxygen evolution (OER) reactions at the anode in chlor−alkali electrolysis is a major challenge in the chemical industry. The development of electrode materials with enhanced stability and CER selectivity could result in a significant reduction of the overall process costs. In order to gain an atomic‐scale understanding of the CER versus OER selectivity, commonly, density functional theory (DFT) calculations are employed that are analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…Using the concept of overpotential-dependent volcano plots with a scaling relation's offset of 2.93 eV at a target overpotential of η target = 0.40 V, the volcano curve unequivocally indicates that RuO 2 is more active than IrO 2 in the OER. [20,53] This may corroborate the suggested procedure of overpotential-dependent volcano plots, particularly for thorough sorting of highly active electrode materials. Additionally, this outcome suggests that general scaling relations by summing up several classes of materials should be treated with some caution.…”
Section: Overpotential-dependent Volcano Plotssupporting
confidence: 76%
See 2 more Smart Citations
“…Using the concept of overpotential-dependent volcano plots with a scaling relation's offset of 2.93 eV at a target overpotential of η target = 0.40 V, the volcano curve unequivocally indicates that RuO 2 is more active than IrO 2 in the OER. [20,53] This may corroborate the suggested procedure of overpotential-dependent volcano plots, particularly for thorough sorting of highly active electrode materials. Additionally, this outcome suggests that general scaling relations by summing up several classes of materials should be treated with some caution.…”
Section: Overpotential-dependent Volcano Plotssupporting
confidence: 76%
“…Section 2.3). [ 53 ] Actually, binding energies (thermodynamics) are already sufficient to recognize inactive materials, whereas close to the top of the volcano microkinetic details of the underlying reaction rather than binding energies are decisive. Since the kinetics and applied overpotential are enclosed in the unifying methodology, the concept of ESSI‐descriptor activity maps excels the conventional volcano scheme, particularly for a profound assessment of highly active electrode materials.…”
Section: Screening Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the HCOO* adsorbate and the H* adsorbate determine the activity of the FAP or the HER, respectively, and hence also the selectivity ratio of the competing processes. Therefore, the selectivity ratios of Cu‐In (101) surfaces for the equilibrium potential of the FAP pathway (−0.16 V vs. RHE) is calculated with the model used in the previous literatures by Kai S. Exner and Vijay Ramani et al [17b,c] (See calculation equations in Supporting Information). As for the Cu‐In (101) surface, it can be clearly found that there is a positive correlation between high FE HCOO − (70 %) and better selectivity ratio of FAP vs.…”
Section: Figurementioning
confidence: 99%
“…It should be noticed that the thermodynamics of the competing HCOOH and CO pathways and the HER are qualitatively calculated by ignoring the effects of surrounding adsorbates in this work. Generally, Ab‐initio Pourbaix diagrams can be employed to resolve the surface structure as a function of the applied electrode potential and pH [17b,c] . However, since we pay more attention on the effect of Cu doping, the Pourbaix diagrams are not included here.…”
Section: Figurementioning
confidence: 99%